3D solid buffering for 3D GIS - Chen, Tet Khuan (2007)
3D analysis is one of the important components in GIS as it defines as decision making tools for geographic features. Next generation of GIS software would highly dependent on the 3D analysis in solving geospatial problems. One of the desired components in the next generation software is to deal with the 3D analytical solutions. This paper presents a portion of the 3D spatial information problems, that is 3D solid buffering. Discussions related to the implementation of buffering model for solid object are the main concern in this paper. The primitives of objects such as point, line, and face will be addressed and integrated for the development of 3D solid buffering. The mathematics, the geometry, and the algorithms involved in the development will be presented. The approach is verified by using simulated data sets and a commercial GIS package for visualization purposes. Finally, we discuss the outlook of the 3D analytical solutions for 3D GIS.